Bamboo networking principle among Chinese entrepreneurs - Abdul Ghani, Roseziahazni; Abu Samah, A’tiqah Rashidah; Yusof Ali, Noorhayati; Mohd Kassim, Nor Akila (Universiti Teknologi MARA, Terengganu, 2022)
The Chinese have significantly more business supremacy than other races in Malaysia, particularly Bumiputeras. Despite the New Economic Policy (NEP) which has been in place for almost 20 years and was designed to increase this number, Bumiputera entrepreneurs continue to fall behind, especially when compared to Chinese entrepreneurs. The Geographical Association (2020) estimates that the Chinese community holds 70% of the market. The dominance of the Chinese community in business is due to business that is usually inherited from the ancestors (Husin, 2013). The tenets of Chinese society, which place a high emphasis on relationships, perseverance, and discipline, have been ingrained in people's souls from the beginning of time, enabling the economy to thrive even now (Husin, 2013).